When incumbents do not run: presidential succession and democratization. Issue 1 (2nd January 2022) - Baturo, Alexander
ABSTRACT: When authoritarian incumbent presidents run in elections, they have significant incumbency advantage and almost always win. When incumbents comply with term limits or do not run for other reasons, they tend to designate successors in their stead. However, their chosen successors often lose. Do they lose because they cannot command the same electoral advantage in loyalty, resources and name recognition that incumbents can, or because succession and elections that follow occur in a more liberal environment? The identification of effects of presidential succession is challenging because individual decisions to leave office, or not, depend on existing power relations. Drawing from studies on authoritarian elections and democratization by elections, I propose an explanation why many incumbents are unable to transfer their incumbency advantage to handpicked successors. I rely on the battery of statistical tests including matching and instrumental variables to isolate the effects of succession on competitive authoritarian elections in 1990–2016. Controlling for liberalization that may occur during succession, successors are still more likely to lose; however, running in a hegemonic party regime or having prior political experience and status may mitigate their electoral disadvantage. When successors lose, I find that the executive turnover that follows often leads to further liberalization.